Awakening the immune system with radiation: Optimal dose and fractionation. Issue 2 (28th November 2015) - Gandhi, Saumil J.; Minn, Andy J.; Vonderheide, Robert H.; Wherry, E. John; Hahn, Stephen M.; Maity, Amit
Highlights: Review preclinical and clinical data for boosting antitumor immunity with radiation. Review data relating to radiation dose and fractionation in setting of immunotherapy. Discuss optimal strategies for combining radiation with immunotherapy. Abstract: The importance of ionizing radiation has historically been limited to achieving local control of tumor cells. However, emerging evidence over the last decade suggests an increasingly important role for radiation in amplifying the antitumor immune response elicited by immunomodulatory agents. Combination of radiation with immunotherapy has been shown to elicit powerful systemic responses in several pre-clinical tumor models. Additionally, recent clinical observations support the use of radiation therapy for augmenting antitumor immunity in the metastatic setting. However, radiation dose and fractionation schedules for optimal synergy between radiotherapy and immunotherapy are not well defined. Here we review pre-clinical and clinical data relating to radiation dose and fractionation in the setting of immunotherapy and discuss optimal strategies for combining the two therapies.